Canga renatae, a new genus and species of Cyphophthalmi from Brazilian Amazon caves (Opiliones: Neogoveidae) - Dasilva, Marcio Bernardino; Pinto-Da-Rocha, Ricardo; Giribet, Gonzalo (Zootaxa, 2010)
A new genus and species of Cyphophthalmi, Canga renatae gen. nov., sp. nov., is described in the family Neogoveidae from a system of caves in the Serra de Carajás, Pará State, Brazil. Canga can be easily distinguished from other neogoveid genera by the presence of a dentate claw on leg I, a unique character among known cyphophthalmid species, and by the free coxa II, which is fused to coxae III and IV in all the other neogoveid species except for the North American Metasiro. The new genus also differs from other Neotropical neogoveids in the lack of a dorsal crest on the chelicerae and in the lack of opisthosomal glands. The finding of a neogoveid in the Pará State greatly increases the known distribution of South American cyphophtalmids into the Eastern Brazilian Amazon forest.